The embodiment of movement in the cinematic artistic achievement in the technical style (Al-Academy, 2024)
This research is concerned with the technical contents and the mechanisms of their operation in the cinematic film, which sparked controversy in artistic circles because it took its first steps in attempts at technical discoveries in the field of photography and then on to successive images that produced a cinematic film, after it was able in its composition to dazzle in the field of cinematic techniques, science and technology. What has transformed the camera and its kinetic joints and given its importance in the field of diversifications added to the multiple techniques in the field of photography and montage،Perhaps the various digital technologies and software, including the specialized crafts field, have excelled in defining the features of the imaginary, the distant, the strange, and the exotic into actual movement embodied in a cinematic film, from a perceived and tangible visual reality to what is parallel to the imagination and the imaginary, and from here the researcher highlights the title of his research: Embodying movement in film. Cinematography using the technical method, including the researcher discusses through several chapters to come up with a concept of what is contained scientifically, artistically and technically in four chapters. The first is the methodological framework, including the research problem in asking the following question: How can movement be embodied in a cinematic film using the technical method? The importance of the research lies in the field of technical advancement and the process of technical development in cinema. The aim of the research is to uncover the technical contents and the mechanisms of their operation in the cinematic film, and in light of the research requirements, a purposive sample was chosen that is consistent with the topic of the research, the film Avatar Part 2, production 2022. As for the second chapter, the theoretical framework, it included three sections. The first is the embodiment of movement in the cinematic film, the second is the mechanisms of embodiment in the cinematic film, and the third topic is entitled the technical method in the cinematic film. And the third chapter, procedures that included the research methodology. The research followed the descriptive analytical method, which is consistent with the research topic, the nature and the research community. A qualitative film was chosen that is characterized by the components and requirements of the research. As for the research tool in the specialty of cinema, it stops within the limits of the scenario and direction as the most important elements in building a tight film, and the researcher takes the framework as an indicator. Theory as reality to shed light on the events contained in the scenes and shots that were selected from the entire film. The fourth chapter includes the results, the most important of which is the director’s emphasis on demonstrating aesthetics Being an investor in what his craft gave him in using technical diversity and modernity to enable the capabilities of techniques and visual integration in creating worlds that dazzle the recipient’s senses. As for the conclusions, including that the kinetic structure is consistent with the principles and rules of that film genre and the many exciting experiences and according to the reality of cinematic production, it is a fulfillment of desires and requirements. Some of them are ideological and psychological, all within the framework of an artistic presentation. Recommendations: The researcher recommends conducting practical field studies using modern technologies to develop the teaching staff within the cinematic specialization. Suggestions: Conduct research on developing student skills using advanced computers for students specializing in cinema in making a digital film. The research includes a list of sources and a summary in English.